Number 35 (August 1997) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1997)
(August 1997) - Observational notes on the spawning behavior of the blue shiner (Cyprinella caerulea) and the holiday darter (Etheostoma brevirostrum), two rare fishes of the Conasauga River, Georgia and Tennessee. By Carol E. Johnston and J.R. Shute Fish species composition and associations in a section of Morganfork Creek, southwestern Mississippi. By Mark D. Farr Minutes, Business Meeting, 22nd Annual Meeting, Southeastern Fishes Council Regional Southeastern Fishes Council Reports
Keywords: fishes; spawning; blue shiner; cyprinella caerulea; holiday darter; etheostoma brevirostrum; rare fishes; conasauga river; morganfork creek